2013
DOI: 10.1371/journal.pone.0071857
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Receptor Is Required for the Development of the Drosophila Peripheral Nervous System

Abstract: The Insulin Receptor (InR) in Drosophila presents features conserved in its mammalian counterparts. InR is required for growth; it is expressed in the central and embryonic nervous system and modulates the time of differentiation of the eye photoreceptor without altering cell fate. We show that the InR is required for the formation of the peripheral nervous system during larval development and more particularly for the formation of sensory organ precursors (SOPs) on the fly notum and scutellum. SOPs arise in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…). This finding is consistent with a recent study that found that loss of Insulin signaling in proneural clusters results in decreased bristle production on the thorax (Dutriaux et al, ). Despite the changes seen in bristle morphology and density, we did not see an effect of Insulin signaling on bristle pigmentation.…”
Section: Discussionsupporting
confidence: 93%
“…). This finding is consistent with a recent study that found that loss of Insulin signaling in proneural clusters results in decreased bristle production on the thorax (Dutriaux et al, ). Despite the changes seen in bristle morphology and density, we did not see an effect of Insulin signaling on bristle pigmentation.…”
Section: Discussionsupporting
confidence: 93%
“…IRKO iPSCs showed an upregulation of neuronal markers including early neural progenitor markers such as Pax6, Tubb3, Oligo2 and Ascl1. This is consistent with the report that the insulin receptor is involved in development of the peripheral nervous system in drosophila [42]. On the contrary, adipocytes differentiated from IRKO iPSCs presented features of reduced adipogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…The box in the bottom right classifies the genes as pro– or anti-longevity based on their known effects on Drosophila lifespan (Tacutu et al 2018). Figure made based on Kapahi and Zid 2004; Dutriaux et al 2013; Texada et al 2020; Denlinger 2022.…”
Section: Resultsmentioning
confidence: 99%
“…During diapause, the brain-PG axis is shut down, inhibiting PTTH production and release, subsequently reducing production of ecdysteroids, resulting in delayed metamorphosis (Fig. 4) (Denlinger 2022).…”
Section: Loss Of Ptth/torso Promotes Selection In the Egfr Pathwaymentioning
confidence: 99%